Phonétique et phonétique corrective: Analyse de production orale d’apprenant de FLE et pistes de correction - Badi, Hussein Saddam (Al-Adab Journal, 2021)
This research deals with the topic of phonology and corrective phonology in a foreign French language. This study aims at improving the pronunciation of the German student who is learning French as a foreign language with the aim of finding the suitable ways of improving his pronunciation. In this study, we have chosen a German student who is studying French in the University Center for French Studies in Grenoble in France. We told this student to read a French text and we recorded this reading. Then we analyzed this dialogue in order to find the pronunciation mistakes and the effect of the German Language in learning French and to know the student’s ability to pronounce new sounds that do not exist in the mother tongue. Finally, we proposed pronunciation corrections that were suitable to the student’s case. This would help the teacher of French in Germany to manage the classroom and improve the pronunciation of his students and make them able to distinguish the sounds of both French and German languages.